Effect of different sizes of graphene on thermal transport performance of graphene paper. (September 2017) - Wang, Ting; Yu, Jinhong; Wang, Mengjie; Cao, Yong; Dai, Wen; Shen, Dianyu; Guo, Liangchao; Wu, Yuming; Bai, Hua; Dai, Dan; Lyu, Jilei; Jiang, Nan; et al.
Abstract: As a two dimensional materials, graphene attracts great attention as heat dissipation material due to its excellent thermal transport property. Herein, three kinds of graphene papers were fabricated with three different thickness graphene nanoplatelets (GNP) via simple vacuum filtration method. The effects of the different size of GNP on the thermal conductivity of graphene papers are investigated systematically. The in-plane thermal conductivity of GNP-7 (the thickness of GNP approximately 7 nm) paper achieves 149.2 Wm -1 K -1, is about 7 times compared to that of GNP-3 (3 nm) and GNP-5 (5 nm), which indicates that thermal conductivity of graphene film increased with increasing the thickness of GNP. Furthermore, the in-plane thermal conductivity of GNP-7 can increase by 25% and raise up to 187.4 Wm -1 K -1 after cold-compaction as cold-compaction will further tighten the loose stacked layers, making the paper more anisotropic in heat conduction. The excellent heat conductive properties of the paper are expected to use as efficient heat spreader for thermal management applications. Graphical abstract: Highlights: The effects of graphene with different size on the thermal conductivity of graphene papers are reported. The graphene paper show excellent thermal transport performance. The graphene paper has potential applications for highly efficient thermal management.